CD155-TIGIT/CD96/CD226 immune checkpoint axis interacting with tumor-infiltrating lymphocytes to exhibit diverse prognostic effects on breast cancer: a cohort study - Ou, Xin; Yin, Junyu; Shi, Feng; Zhao, Yanjie; Zhou, Quan; Yuan, Keyu; Lyu, Shuzhen; Wu, Jiangping; Li, Yanping; Song, Qingkun (Frontiers in Immunology, 2025)
BackgroundCD155, an immune checkpoint molecule interacted with receptors of TIGIT/CD96/CD226 to exhibit co-inhibitory and co-stimulatory modulation on tumor immune microenvironment. Nevertheless, the exploration of collectively prognostic effect of these four molecules on breast cancer (BC) was limited. This study aimed to investigate the prognosis effect of CD155-TIGIT/CD96/CD226 complex in BC.MethodsCD155-TIGIT/CD96/CD226 expression was evaluated by immunohistochemistry in tumor microenvironment (TME) by pathological professionals and the associations with clinical characteristics and prognosis were investigated under a cohort study design.ResultsCD155 was detected on TME tumor cells (TC) and TIGIT/CD96/CD226 were detected on both TC and stromal tumor-infiltrated lymphocytes (TILs). The four molecules showed significant correlation with clinicopathological characteristics and prognosis. High CD155 was associated with relapse (HR = 2.21, 95%CI:1.18-4.13) and death (HR = 2.57, 95%CI:1.29-5.10). High expression of CD226 (HR = 1.79, 95%CI:1.03-3.11) and CD96 (HR = 2.65, 95%CI:1.09-6.44) on TC was correlated with high risk of relapse. High expression of TIGIT on TILs was related to poor prognosis of relapse (HR = 2.06, 95%CI:1.02-4.14), while the expression on TC was a protective factor for relapse (HR = 0.45, 95%CI:0.24-0.83) and death (HR = 0.32, 95%CI:0.16-0.66). Additionally, tumoral and stromal expression of these biomarkers interacted with TME infiltration of stromal TILs to exhibit the diverse prognosis effect.ConclusionThe CD155-CD226/TIGIT/CD96 immune checkpoint complex expressed on both TME TC and TILs, and interacted with TILs to exhibit diverse prognosis effect on BC. The immunotherapy against these checkpoint proteins should check the expression on both TC and TILs and further studies should explore the molecule complex collectively for comprehensive prediction of BC prognosis.